Roberto de Nobili SJ i misja w Maduraju w latach 1606-1656 - Justyna Pyz, (Annales Missiologici Posnanienses, 2019)
The Mission in Madurai 1606-1656 was a unique episode in the history of Christianity in India. During these times changing religion to Christianity meant abandoning one’s culture. Roberto de Nobili, an Italian Jesuit and founder of the mission was the ﬁ rst European to learn Sanskrit, study the scriptures of the Vedas and convert Brahmins. He allowed them to keep their social customs, which was seen as controversial by the church hierarchy. He followed these social rules himself, living the life of an Indian ascetic and thus gaining respect among higher castes. His way of separating Hinduism from Indian culture was, and still is, contentious but it was done for practical purposes. The controversies forced him to defend his arguments on many occasions. In his writings he described Indian traditions and explained his method of missionary work. There were not many followers of de Nobili’s method, who would be able to understand the need of accommodation, undertake studies of Hinduism and be prepared to embrace an ascetic lifestyle. It was not until the 20th century that interreligious dialogue emerged as a concept and some Catholic clergymen found inspiration in Hindu spirituality. The goal of this thesis is to show just how pioneering was the accommodation method used by de Nobili and how his inﬂ uence can still be felt on attempts at interreligious dialogue in the modern era.